Modelling daily return variations in developing market currencies - Howarth, Grant (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
This study examines the American Dollar (USD) denominated currency returns of five developing market currencies for the presence of the day-of-the-week effect. Daily data from January 1995 to February 2008 is examined, and is split into two subperiods, SP1 (1995 - 2002) and SP2 (2003 - February 2008). Currency returns are non-normally distributed across the full data set and SP1 , but tend towards normality in SP2. As such non-parametric tests are used to test the equality of the first four moments across days of the week. Tests on the first moment show that two of the currencies do not show any evidence of the day-of-the-week effect. However, evidence of the day-of-the-week effect is found in the other three currencies in SP1, although the effect disappears or weakens significantly in SP2. Little evidence of the day-of-the-week effect is found in tests on the second moment. The hypothesis of equal higher moments across currency returns is rejected for almost all of the weekday pairs for all five currencies in SP1 , but in SP2 the hypothesis of equal higher moments can only be rejected for a single pair of weekdays for one currency. This indicates the disappearance of the day-of-the-week effect across higher moments in SP2. Thus, the study finds that the day-of-the-week effect is present across the first moment and higher moments in the returns to most currencies in SP1 , but has disappeared for all five currencies in SP2.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Dollar, American; Currency questions; Foreign exchange market; Foreign exchange rates; Rate of return -- Developing countries; Money market; Prices